Role of Religious Courts in Settlement of Inheritance Disputes in Indonesia - Octavia, Wirda Ningsih; Iskandar, Iskandar (International Journal of Social Science and Community Service, 2024)
Islamic Religious courts play an important role in the Indonesian justice system, especially in the settlement of inheritance disputes between Muslims. Indonesia regulates inheritance law based on Islamic law found in the Compilation of Islamic Law (KHI). The aim of this study is to examine the role of the Religious Court in the settlement of succession disputes in Indonesia. The research focuses on how effectively Islamic law is applied, the problems faced, and the mediation process. Secondary data comes from relevant legal documents and literature. Primary data is obtained through thorough interviews with mediators, disputing parties, and religious court judges. Research shows that religious courts mediate conflicts well, but they face problems such as difficult cases and lack of legal awareness. To improve the settlement of disputes in the religious courts, improved legal education and increased resources are needed. The study provides suggestions for improving the performance of the Religious Court and is expected to help the development of inheritance law in Indonesia and improve the quality of justice for society.